2020
DOI: 10.3389/fgene.2020.607428
|View full text |Cite
|
Sign up to set email alerts
|

DNA-PKcs: A Multi-Faceted Player in DNA Damage Response

Abstract: DNA-dependent protein kinase catalytic subunit (DNA-PKcs) is a member of the phosphatidylinositol 3-kinase related kinase family, which can phosphorylate more than 700 substrates. As the core enzyme, DNA-PKcs forms the active DNA-PK holoenzyme with the Ku80/Ku70 heterodimer to play crucial roles in cellular DNA damage response (DDR). Once DNA double strand breaks (DSBs) occur in the cells, DNA-PKcs is promptly recruited into damage sites and activated. DNA-PKcs is auto-phosphorylated and phosphorylated by Atax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 140 publications
(171 reference statements)
0
76
0
Order By: Relevance
“…However, the expression of p-AKT and p-GSK3β decreased; this result was consistent with that of the phosphorylation protein microarray analysis. p-DNA-PKcs, a core component in the NHEJ pathway for the DSB damage repair process, is phosphorylated under cellular stress and assembled into DNA-PK with Ku70 and Ku80 heterodimers to participate in the repair process of DSBs; they also cascade to amplify repair signals and recruit more sensor proteins to repair sites to promote repair ( 25 ). The results showed that expression of the p-DNA-PKcs protein in LUAD cells increased after radiation.…”
Section: Resultsmentioning
confidence: 99%
“…However, the expression of p-AKT and p-GSK3β decreased; this result was consistent with that of the phosphorylation protein microarray analysis. p-DNA-PKcs, a core component in the NHEJ pathway for the DSB damage repair process, is phosphorylated under cellular stress and assembled into DNA-PK with Ku70 and Ku80 heterodimers to participate in the repair process of DSBs; they also cascade to amplify repair signals and recruit more sensor proteins to repair sites to promote repair ( 25 ). The results showed that expression of the p-DNA-PKcs protein in LUAD cells increased after radiation.…”
Section: Resultsmentioning
confidence: 99%
“…ATM phosphorylates several proteins that will mediate cell cycle arrest and DNA repair [25]. In this sense, DNA-PK and H2AX histone are phosphorylated and hence activated by ATM [29]. Phosphorylated H2AX (γ-H2AX) will recruit more ATM molecules together with DNA repair factors [25].…”
Section: Dna Damage and Cancer Old Friendsmentioning
confidence: 99%
“…1). DNA-PKcs interacts with Ku70/80 in the presence of dsDNA to form the active DNA-dependent protein kinase holoenzyme DNA-PK, and is required for non-homologous end joining (NHEJ), the major pathway for the repair of ionizing radiation (IR)-induced DNA double-strand breaks (DSBs) in human cells (Yue et al, 2020;Zhao et al, 2020a). In NHEJ, the Ku heterodimer binds directly to DSB ends (Fig.…”
Section: Repair and Non-repair Functions Of Dna-pkcsmentioning
confidence: 99%
“…DNA-PKcs and Artemis are also required for opening DNA hairpin coding ends during V(D)J recombination and cells lacking DNA-PKcs, Ku, XRCC4 or DNA ligase IV are radiation sensitive and defective in NHEJ and V(D)J recombination (Pannunzio et al, 2018). Recently, additional roles for DNA-PKcs, outside DSB repair have been reported (Yue et al, 2020), including mitosis (Douglas et al, 2014(Douglas et al, , 2020Jette & Lees-Miller, 2015;Lee et al, 2011), transcription (Goodwin et al, 2015;Ju et al, 2006), RNA processing (Shao et al, 2020), metastasis (Goodwin et al, 2015), metabolism (Chung, 2018;Park et al, 2017), the innate immune response (Yang et al, 2020) and HIV replication (Anisenko et al, 2020), but its most well-characterized role is in NHEJ.…”
Section: Repair and Non-repair Functions Of Dna-pkcsmentioning
confidence: 99%